Restless heart - Judd, Wynonna, 1964-; McLane, LuAnn (New York : New American Library, 2011)
Destiny finds success on the musical stage but struggles to reconnect to the things in her life that matter most.
Keywords: Women country musicians -- Fiction; Kentucky -- Fiction